2020
DOI: 10.1302/0301-620x.102b1.bjj-2019-0853.r2
|View full text |Cite
|
Sign up to set email alerts
|

The use of the Ganga Hospital Score to predict the treatment and outcome of open fractures of the tibia

Abstract: Aims Open fractures of the tibia are a heterogeneous group of injuries that can present a number of challenges to the treating surgeon. Consequently, few surgeons can reliably advise patients and relatives about the expected outcomes. The aim of this study was to determine whether these outcomes are predictable by using the Ganga Hospital Score (GHS). This has been shown to be a useful method of scoring open injuries to inform wound management and decide between limb salvage and amputation. Methods We collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Limb salvage was associated with better LEFS than amputations. 15 Similarly, patients with amputations scored significantly lower on both 12-Item Short Form Health Survey (SF-12) 24 composite physical and mental health scores and had lower EuroQol five-dimension health questionnaire (EQ-5D) 25 quality of life indices than those with salvaged limbs. 14 Messner et al 16 showed that despite good clinical outcomes, open fractures in children had lasting impact on function and quality of life, and potential for long-term psychological problems.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Limb salvage was associated with better LEFS than amputations. 15 Similarly, patients with amputations scored significantly lower on both 12-Item Short Form Health Survey (SF-12) 24 composite physical and mental health scores and had lower EuroQol five-dimension health questionnaire (EQ-5D) 25 quality of life indices than those with salvaged limbs. 14 Messner et al 16 showed that despite good clinical outcomes, open fractures in children had lasting impact on function and quality of life, and potential for long-term psychological problems.…”
Section: Resultsmentioning
confidence: 98%
“…One study totally excluded patients who underwent amputation, raising high concerns that the reference standard did not match the review question, and another excluded an unspecified number of patients and did not report on amputations. 15 Diagnostic meta-analysis for Ganga Hospital Open Injury Severity Score in detecting the need for secondary and primary amputations in lower limbs. The solid square represents the pooled value of sensitivity and specificity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the covering tissue score yields suggestions on the soft tissue closure approach, ranging from primary closure to delayed flap. 38,39 Finally, it generates estimates in 6 treatment outcomes: total length of treatment, number of surgeries required, number of hospital admissions, length of hospital stay, final functional outcomes, and bony union time. GHOISS has been described to be superior in assessing Gustilo-Anderson IIIb injuries, where other scoring systems have demonstrated poor intraand inter-observer reliability and inability to predict limb salvage and functional outcomes.…”
Section: Ganga Hospital Open Injury Severity Scorementioning
confidence: 99%
“…40 Since its inception, GHOISS has demonstrated a high sensitivity and specificity for amputation and good predictability of surgical outcomes in type IIIb open tibial fractures in both adults and children. 39,41,42…”
Section: Ganga Hospital Open Injury Severity Scorementioning
confidence: 99%